Investigation of sulfur-containing compounds in spears of green and white Asparagus officinalis through LC-MS and HS-GC–MS. (December 2022) - Bergamasco, Elena; Peron, Gregorio; Venerando, Andrea; Ahmed Polash, Shakil; Shukla, Ravi; Sut, Stefania; Dall'Acqua, Stefano; Masi, Antonio
Graphical abstract: Highlights: Investigation on the LMW sulfur containing compounds in Asparagus officinalis was performed. LC-MS and GC–MS approaches were used. Thiols were analysed both as unmodified and derivatized. New approach for studying sulfur containing compounds in foods is presented. Abstract: Asparagus officinalis is largely consumed as food in many parts of the world, and due to its content in secondary metabolites can be considered as a vegetable with health-promoting value. Part of its organoleptic qualities can be ascribed to the presence of sulfur-containing compounds, nevertheless qualitative data about the volatile and non-volatile pools of these compounds in green and white spears of asparagus are poorly investigated. Due to the wide alimentary use of this crop and the potential biological properties of S-containing compounds, research aimed at filling this gap is required. In this paper, a comprehensive characterization of S-metabolites in asparagus performed by LC-MS and GC–MS is reported. Both green and white varieties of asparagus were considered. The fresh vegetal material was subjected to different sample preparation procedures, such as solvent extraction, distillation, and headspace sampling. Furthermore, a derivatization protocol with 4, 4′-dithiodipyridine was used for low-molecular weight thiols, and both derivatized and underivatized compounds were analysed by LC-MS. The methods allowed to identify 80 S-containing metabolites in asparagus samples, and to assess the distribution of these compounds in different parts of the spears. Results were discussed comparing the literature, and the identified compounds were considered to explain some peculiar taste and odorous properties of green and white asparagus, although further research is required to confirm our hypotheses. Overall, in this work we report for the first time an exhaustive characterization of S-compounds profile in spears of green and white Asparagus varieties. Furthermore, results indicate that multiple approaches should be used to study the S-containing metabolites of this plant, due to their diverse chemical properties.